Embodying masculinity in female dominated research settings: A male reflection of ‘doing research’ in massage parlours - Sam Hanks (Sexualities, 2020)
This paper reflects on the male experience of conducting fieldwork in massage parlours; off-street settings where women exchange sexual services in predominantly heterosexual monetary transactions. It examines debates surrounding the desirability of gender incongruence between researchers and their informants. By acknowledging the complex interplay of gender and relations in the field, experiences of power are presented as variable and dynamic rather than fixed. Honest and detailed accounts of interactions with sex workers are used to show the complexities of embodying masculinity in clandestine and feminized spaces. The perceived benefits and limitations of gender incongruence are presented. The need to consciously manage and comprehensively reflect upon the impact of gender, and the complex array of power dynamics in the field is discussed.